The performance of duplex ultrasonography for the assessment of renal artery stenosis in Takayasu’s arteritis patients - Wang, Yahong; Wang, Ying; Zhang, Li; Ge, Zhitong; Li, Jing; Yang, Yunjiao; Chen, Yu; Yang, Xiao; Li, Jianchu; Tian, Xinping (Arthritis research & therapy, 2023)
This study intends to analyze the hemodynamic parameters of the renal artery in patients with Takayasu's arteritis (TAK) to explore the diagnostic efficacy of duplex ultrasonography in assessing the involved renal artery in TAK patients. One hundred fifteen TAK patients with 314 renal arteries were retrospectively analyzed, who were admitted to Peking Union Medical College Hospital between 2017 and 2022. These patients underwent both renal artery ultrasonography and angiography within a 4-week period. Specifically, the study compared seven ultrasonic parameters across groups categorized by the severity of renal artery stenosis (RAS), including noninvolvement, < 50% stenosis, 50-69% stenosis, and 70-99% stenosis. Receiver operating characteristic (ROC) curves were employed to determine the optimal threshold values for renal artery peak systolic velocity (RPSV), renal-aortic PSV ratio (RAR), and renal-interlobar PSV ratio (RIR) in order to diagnose various degrees of RAS in TAK patients. Statistically significant differences were observed in RAR and RIR among the four groups (all P < 0.05). However, no statistically significant differences were found in RPSV and AT between the moderate stenosis group (50-69% stenosis) and the severe stenosis group (70-99% stenosis). The discrimination of interlobar PSV (IPSV) and interlobar RI (IRI) was not significant, and IEDV did not show statistical significance among the four groups. For TAK patients, the recommended thresholds of RPSV for the diagnosis of renal artery involvement (RAI), ≥ 50% RAS, and ≥ 70% RAS were determined to be 143 cm/s, 152 cm/s, and 183 cm/s, respectively. The sensitivities, specificities, and accuracies of these thresholds were all found to be greater than 80%. Additionally, the optimal thresholds of RIR for detecting RAI, ≥ 50% RAS, and ≥ 70% RAS were determined to be 4.6, 5.6, and 6.4, respectively, with satisfactory diagnostic efficiencies. The areas under the curve (AUCs) for RPSV and RIR were calculated to be 0.908 and 0.910, respectively, for the diagnosis of ≥ 50% RAS, and 0.876 and 0.882 for the diagnosis of ≥ 70% RAS. When the aortic PSV is greater than or equal to 140 cm/s, the RAR exhibits inadequate diagnostic efficacy. Conversely, when the aortic PSV is less than 140 cm/s, a RAR value of 2.2 or higher can be employed as the diagnostic threshold for identifying RAS of 70% or greater, with a sensitivity of 84.00%, specificity of 89.93%, and an overall accuracy of 89.08%. In the present study, it has been demonstrated that RPSV and RIR possess substantial diagnostic value as ultrasonic parameters for diagnosing RAS in TAK patients. Furthermore, when assessing the diagnostic efficacy of RAR, it is crucial to consider the severity of aortic stenosis as a determining factor.